Pendidikan dan penggunaan komputer di sekolah menengah negeri Kedah Darul Aman - Saleh, Abdul Razak; Mohd, Haslina; Mat Aji, Zahurin; Ibrahim, Huda; Ismail, Salina (Universiti Utara Malaysia, 1998)
This paper reports on a study of the level of computer education and usage in secondary schools in Kedah Darul Aman. A total of 78 schools (94.0%) were equipped with computer hardware whereas two schools in the rural areas (4.8%) had none. There were 61 schools (76.3%) with computer clubs. The study revealed that the percentage of teachers who were involved in the computer clubs was less than 15%. Most (52.6%)of them acted as club advisors, 29.0% were instructors, while the rest were committee members (18.4%). There were teachers who were involved in the club but had never attended any formal computer training. A majority (89.0%) who had computer training felt that the courses were inadequate. In general, most computer club teachers had average skills in handling graphics software and were less skilled in using word processing packages, spreadsheets and database software.